Modern researches of personality-psychological features in patients with somatoform disorders - V. V. Vasilyev; A. I. Mukhametova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The scientific review is devoted to the actual problem of personality-psychological features of patients with somatoform disorders (SFD). It is based on the analysis of 91 publications on this topic (42 in Russian and 49 in English) that have been published over the past 10 years. The search for publications was carried out in the RSCI and Medline bibliographic databases. The purpose of the review was to consider the main directions of the studies of personality-psychological factors for the SFD formation which has been developing over the past decade, and to highlight those of these factors that are currently the most generally recognized. The review considers the following directions of research in this area: studies of alexithymia, studies of somatosensory amplification, studies of the patients’ character features, studies of cognitive processes in SFD, studies of psychological defenses and coping strategies, studies in the framework of attachment theory, studies of socio-psychological factors of SFD development, integrative concepts of personality predisposition to SFD. As a result, a high level of alexithymia and personality anxiety, rigidity of cognitive processes, general inferiority of psychological defenses and coping strategies, and a high socio-stress load was highlighted as the most generally recognized personality-psychological factors of the SFD formation. Factors that are sufficiently recognized, but still need further study, are also the somatosensory amplification, the frequent use of reactive formation as a psychological defense and avoidant behavior as a coping strategy, the pattern of insecure attachment. The conclusion notes the need to continue research in this area and proposes possible further directions, in particular, the identification of causal relationships between already established personality-psychological predictors of SFD, as well as the study of their interactions with factors of a different nature (genetic, morphological, psychopathological).